Competing for the Skies : A Strategic Analysis of Emirates and Turkish Airlines - Anteplioğlu, Emir (2025)
The outcome of this thesis is an analysis of the key factors that have contributed to the success and competitive advantage of Emirates and Turkish Airlines. By comparing their strategies, this research will highlight both similarities and differences, providing insights into their business models. The findings will help determine whether their paths to success are alike or distinct, offering a deeper understanding of the strategic choices that have shaped their growth in the global aviation industry.